Effect of accelerated aging on the mechanical properties and wear of different commercial dental resin composites - Oja, Jonne (My University, 2021)
Aim. The purpose of this in vitro study was to determine the effect of thermally accelerated aging on the mechanical properties and wear of different commercial dental resin composites (RCs). In addition, the effect of expiration date of the composite prior its use was also evaluated. Material and methods. Five commercially available RCs were studied. Conventional RCs (Filtek Supreme XTE, G-aenial Posterior, Denfil, and >3y expired Supreme XTE), bulk-fill RC (Filtek Bulk Fill), and discontinuous fiber-reinforced RC (everX Posterior). Three-point flexural test was used for determination of ultimate flexural strength (n=8). A vickers indenter was used for testing surface microhardness. A wear test was conducted with 15000 chewing cycles using a dual-axis chewing simulator. Wear pattern was analyzed by a three dimensional (3D) noncontact optical profilometer. Degree of C=C bond conversion of monomers was determined by FTIR-spectrometry. The specimens were either dry stored for 48 hours (37°C) or boiled (100°C) for 16 hours before testing. Scanning electron microscopy (SEM) was used to evaluate the microstructure of each material. Data were analyzed using ANOVA (p = 0.05). Results. Thermal aging had no significant effects on the surface wear and microhardness of tested RCs (p>0.05). While flexural strength significally decreased after boiling (p<0.05) except for G-aenial Posterior which showed no differences. Expiration date does not affect the flexural strength and wear of tested RC. Conclusion. It was concluded that the effect of accelerated aging may have caused certain hydrolytic degradation of the RC of some brands whereas no effect was found with one brand of RC. Thus, the accelerated aging appeared to be more dependent on material and tested material property.
Keywords: resin composite, thermal aging, wear, expiration date